A key design to prolong lifetime of wireless sensor network. (August 2016) - Qiu, Bo; Chen, XiQiu; Wu, Qi
Abstract: In order to solve the contradiction between the connectivity of the wireless sensor network and the key storage consumption, under the premise of reducing network storage consumption, the key pre-distribution management scheme with higher connectivity rate is proposed using the hexagonal network deployment information, which adopts the idea of the matrix space for the square deployment information strategy to reduce the burden of the network storage. Ability against the capture attack is improved obviously. The results show that contradiction between the network connectivity rate and the energy consumption has a better solution, and the proposed algorithm is suitable for the wireless sensor networks of energy limited.